2003
DOI: 10.1046/j.1474-8673.2003.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo treatment with interleukins 1β and 6 on rat mesenteric vascular bed reactivity

Abstract: 1. Inflammatory bowel disease (IBD) is a condition that involves proinflammatory cytokines such as interleukins 1beta and 6 (ILs). In this disease, it has been shown that an abnormal microcirculatory system is implicated. 2. Therefore, the effects of in vivo treatment for three days with interleukins 1beta and 6 were investigated on rat isolated mesenteric vascular bed (MVB). 3. A significant concentration-dependent increase in vascular response to noradrenaline (NA) was found, with a significant difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
2
18
0
2
Order By: Relevance
“…Direct effect of a wide range of well defined cytokines on vascular tone in isolated human artery has been studied and IL-6 was demonstrated to induce the contraction of artery and this vascular effect was endothelium-dependent [19]. A recent work done by Myung et al [20] in 2008 reported that contractile response to phenylephrine was significantly enhanced in the IL-6-treated strip and the relaxation response to acetylcholine was significantly inhibited by IL-6.…”
Section: Relationship Between Interleukin-6 and Endothelial Nitric Oxmentioning
confidence: 97%
“…Direct effect of a wide range of well defined cytokines on vascular tone in isolated human artery has been studied and IL-6 was demonstrated to induce the contraction of artery and this vascular effect was endothelium-dependent [19]. A recent work done by Myung et al [20] in 2008 reported that contractile response to phenylephrine was significantly enhanced in the IL-6-treated strip and the relaxation response to acetylcholine was significantly inhibited by IL-6.…”
Section: Relationship Between Interleukin-6 and Endothelial Nitric Oxmentioning
confidence: 97%
“…24 Conversely, they can also enhance vasoconstrictor responses to other agents because of the loss of endothelial integrity to blunt these responses. 24,25 This might explain why the relative contraction to phenylephrine was significantly increased in MC1R To extend the findings in MC1R e/e mice to a clinical perspective, we explored the association of human MC1-R variants to early markers of atherosclerotic changes. The vascular phenotype of MC1R e/e mice was highly concordant with the data from young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical effects of inflammatory mediators on colonic motility have been carefully studied and found to be primarily due to effects on neurotransmission (7,30). Other functional effects might include regulation of lymphocyte and mast cell influx to the muscularis and vasculitis of the inflamed colon (9). RANTES and IL-8 are promigratory chemokines that attract monocytes and neutrophils to sites were they are produced.…”
Section: Discussionmentioning
confidence: 99%